Anti-apoptotic and anti-fibrotic efficacy of exercise training in hypertensive hearts: A systematic review - Akbar, Adjar Yusrandi; Cui, Zhen-Yang; Hsu, Che-Jui; Li, Yan-Zhang; Rahman, Ferry Fadzlul; Xia, Chunqiu; Yang, Ai-Lun; Lee, Shin-Da (Frontiers in Cardiovascular Medicine, 2023)
Background This review aims to summarize the antiapoptotic, pro-survival, and antifibrotic effects of exercise training in hypertensive hearts. Methods Keyword searches were conducted in PubMed, Web of Science, and Scopus in May 2021. Research published in English on the effects of exercise training on the apoptosis, survival, and fibrosis pathways in hypertension was included. The CAMARADES checklist was used to determine the quality of the studies. Two reviewers independently implemented predesigned protocols for the search and selection of studies, the assessment of study quality, and the evaluation of the strength of evidence. Results Eleven studies were included after selection. The duration of the exercise training ranged from 5 to 27 weeks. Nine studies showed that exercise training improved cardiac survival rates by increasing IGF-1, IGF-1 receptor, p-PI3K, Bcl-2, HSP 72, and p-Akt. Furthermore, 10 studies showed that exercise training reduced apoptotic pathways by downregulating Bid, t-Bid, Bad, Bak, Bax, TNF, and FADD. Finally, two studies reported the modification and subsequent improvement of physiological characteristics of fibrosis and decreased MAPK p38 and PTEN levels by exercise training in the left ventricle of the heart. Conclusions The findings of the review showed that exercise training could improve cardiac survival rates and attenuate cardiac apoptotic and fibrotic pathways in hypertension, suggesting that exercise training could act as a therapeutic approach to prevent hypertension-induced cardiac apoptosis and fibrosis. Systematic Review Registration https://www.crd.york.ac.uk, identifier: CRD42021254118.